2006
DOI: 10.1080/02643290542000067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the semantic representations of living and nonliving concepts: A normative study

Abstract: Current feature-based semantic memory models assume that the semantic representations of concepts differ systematically across living and nonliving categories and that such differences account for the emergence of category-specific semantic deficits in brain-damaged people. To assess some of the different models' main assumptions about structural differences at the semantic feature level in the two major semantic domains, we administrated a feature-listing task to normal young volunteers on 64 concepts drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 30 publications
2
55
1
Order By: Relevance
“…Interestingly, several of the most commonly used categories in the literature (e.g., in Battig & Montague, 1969;Bueno & Megherbi, 2009;Garrard et al, 2001;McRae et al, 2005;Van Overschelde et al, 2004;Zannino et al, 2006) were among these LR categories-namely <frutta/fruit>, <strumenti musicali/musical instruments>, <armi/weapons>, and <vegetali/vegetables> -since their concepts were listed on average by only a minority of our participants (20.1 %, 11.1 %, 8.5 %, and 6.2 %, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, several of the most commonly used categories in the literature (e.g., in Battig & Montague, 1969;Bueno & Megherbi, 2009;Garrard et al, 2001;McRae et al, 2005;Van Overschelde et al, 2004;Zannino et al, 2006) were among these LR categories-namely <frutta/fruit>, <strumenti musicali/musical instruments>, <armi/weapons>, and <vegetali/vegetables> -since their concepts were listed on average by only a minority of our participants (20.1 %, 11.1 %, 8.5 %, and 6.2 %, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Existing norms in the literature are typically based on concepts or categories that either are selected from previously published databases (De Deyne et al, 2008;Garrard et al, 2001;Izura, Hernández-Muñoz, & Ellis, 2005;Kremer & Baroni, 2011;McRae et al, 2005;Ruts et al, 2004;van Dantzig, Cowell, Zeelenberg, & Pecher, 2011;Zannino et al, 2006) or are chosen a priori by researchers (Lynott & Connell, 2009;McRae et al, 2005;Vinson & Vigliocco, 2008). In this manner, participants describe categories or concepts that are only supposed to be representative of semantic memory, without controlling for their actual representativeness, or importance, in the semantic organization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is shown, for example, in the investigations conducted by Cree and McRae (2003), who studied the factors that determine the pattern of semantic categories observed in category-specific semantic deficits and concluded that, besides knowledge type, other variables, such as feature informativeness, concept confusability, visual complexity, familiarity, and name frequency, also have influences. Moreover, Zannino, Perri, Pasqualetti, Caltagirone, and Carlesimo (2006) observed that the data regarding category composition vary depending on the selection of concept-dependent or concept-independent correlation measures. They also showed that feature dominance plays an important role on the analysis of the feature type that is relevant for either living or nonliving domains.…”
Section: Importance Of Feature Normsmentioning
confidence: 99%